Optimized method for fluorine-18 radiolabeling of Affibody molecules using RESCA - Francesco Lechi; Jonas Eriksson; Luke R. Odell; Olivia Wegrzyniak; John Löfblom; Fredrik Y. Frejd; Bo Zhang; Olof Eriksson (SpringerOpen, 2024)
Abstract Background In recent years, the interest in Al[18F]F as a labeling agent for Positron Emission Tomography (PET) radiotracers has risen, as it allows for fast and efficient fluorine-18 labeling by harnessing chelation chemistry. The introduction of Restrained Complexing Agent (RESCA) as a chelator has also shown that chelator-based radiolabeling reactions can be performed in mild conditions, making the radiolabeling process attractively more facile than most conventional radiofluorination methods. The aim of the study was to establish optimized conditions for Al[18F]F labeling of Affibody molecules using RESCA as a complexing agent, using Z09591 and Z0185, two Affibody proteins targeting PDGFRβ and TNFα, respectively, as model compounds. Results The Al[18F]F labeling of RESCA-conjugated Z09591 was tested at different temperatures (rt to 60 °C) and with varying reaction times (12 to 60 min), and optimal conditions were then implemented on RESCA-Z0185. The optimized synthesis method was: 1.5-2.5 GBq of cyclotron produced fluorine-18 were trapped on a QMA cartridge and eluted with saline solution to react with 12 nmol of AlCl3 and form Al[18F]F. The respective RESCA-conjugated Affibody molecule (14 nmol) in NaOAc solution was added to the Al[18F]F solution and left to react at 60 °C for 12 min. The mixture was purified on a NAP5 size exclusion column and then analyzed by HPLC. The entire process took approximately 35 min, was highly reproducible, indicating the efficiency and reliability of the method. The labeled compounds demonstrated retained biological function for their respective targets after purification. Conclusions We present a general and optimized method for Al[18F]F labeling of RESCA-conjugated Affibody molecules, which can be widely applied to this class of peptide-based imaging agents. Moreover, radiochemical yields were improved when the labeling was conducted at 37 °C or above. In vitro and in vivo assessment of the respective tracers was promising, showing retained binding capacity as well as moderate defluorination, which is usually regarded as a potential downside for RESCA-conjugated tracers. Graphical abstract